Tocilizumab in the management of posttransfusion hyperhemolysis syndrome in sickle cell disease: The experience so far. Issue 3 (29th January 2022) - Meenan, John; Hall, Rhys; Badle, Saket; Chatterjee, Basabi; Win, Nay; Tsitsikas, Dimitris A.
Abstract: Background: Posttransfusion hyperhemolysis syndrome is a rare but life‐threatening form of delayed hemolytic transfusion reaction with lysis of both transfused and autologous red cells, seen predominantly in patients with sickle cell disease. Macrophage activation is thought to play a major role in its pathophysiology. Standard treatment is with intravenous immunoglobulin and steroids but refractory cases pose a major clinical problem. Tocilizumab is a humanized monoclonal antibody against the IL‐6 receptor that can inhibit IL‐6 induced macrophage activation. Methods and materials: We describe the case of a 33‐year‐old woman with sickle cell anemia and posttransfusion hyper hemolysis syndrome refractory to standard therapy, treated with Tocilizumab. We also review all cases reported in the literature where Tocilizumab was used for posttransfusion hyperhemolysis. Results: Treatment with Tocilizumab was well tolerated with no observed adverse events. There was no further drop in Hb after day 2 of treatment with subsequent continuous gradual improvement. Her bilirubin dropped significantly after the first dose and continued to improve, while ferritin and LDH reduced significantly after day 2 of treatment with Tocilizumab and continued to drop thereafter. Like in our case, all other cases in the literature where Tocilizumab was used for posttransfusion hyperhemolysis led to rapid clinical responses and no adverse events. Discussion: Even though the number of cases of posttransfusion hyper hemolysis syndrome treated with Tocilizumab are few, they have all been associated with rapid clinical responses with no observed adverse events suggesting that the role of Tocilizumab in this context needs to be further explored.